ANALISIS KESULITAN MEMBACA PERMULAAN SISWA DI KELAS III SEKOLAH DASAR - Ana, Juli; Abi, Antonius Remigius; Sihotang, Micha Z (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
The research method that the author uses in this research is a qualitative method with the approach in this research is a case study approach to produce descriptive data in the form of written or spoken words from subjects/actors and behaviors that can be observed with the aim of knowing in depth and trying to find the underlying meaning regarding students' initial reading difficulties. There were 7 informants in the interview where 2 people became key informants, namely students who had difficulty reading at the beginning, 2 parents of students, 1 homeroom teacher of grade III students and 2 friends from grade III became supporting informants. To find out students' difficulties in beginning reading, researchers made direct observations and conducted interviews. After conducting interviews, the researcher obtained information that of the 32 third grade students at SD Negeri 047166 Sukadame that there are 12 students who already have good reading skills and 20 students who have difficulty in reading. Factors that cause students to have difficulty in beginning reading are physiological, intellectual, environmental and psychological factors.